Penggunaan Internet dan Faktor yang Berhubungan pada Penyuluh Pertanian Kabupaten Bandung - Aulia, Muhammad Haikal Rizqy; Hapsari, Hepi (Universitas Galuh, 2024)
Agricultural extension workers are required to keep up with the times in carrying out their role as a bridge of information for farm business actors. The imbalance between the number of extension workers and the fostered villages makes the extension workers work around it by utilizing the use of the internet for effective and efficient extension. As well as the occurrence of the Covid-19 pandemic has made extension workers accustomed to conducting counseling and providing material using an online meeting platform that is still carried over today because of its ease of reaching farmers. This study aims to describe how the level of internet usage has been applied by extension workers and analyze what factors are related to the level of internet usage. This research was conducted in agricultural extension centers in Bandung Regency. The variables used were characteristics, level of internet usage, information needs, and frequently used sites. The research design used was descriptive quantitative with non-parametric rank spearman correlation analysis tool and sampling technique using Roscoe method. The level of internet usage seen from the frequency of use in one working week is high with a percentage of 62.5% using the internet more than 4-5 working days in one week, while when the duration of internet usage it is still relatively low with a majority of 65% using the internet 2-3 hours per working day. Factors associated with internet use are characteristics of extension workers (education) and sites or applications that are frequently used (Ministry of Agriculture website and Whatsapp).